The Cognitive Unconscious 2022
DOI: 10.1093/oso/9780197501573.003.0008
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Learning of Motor and Perceptual Skills

Abstract: Humans and other animals exhibit an astonishing capacity to learn motor and perceptual skills through practice and experience. Both can occur without awareness and explicit knowledge of what has been learned. They follow similar learning trajectories and involve offline gains in performance. Work with neuropsychological patients has revealed the importance of interactions between cortex and the basal ganglia in both types. One difference that appears to exist is the capacity for transfer to similar learning si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Many studies that have used the SRT task have shown that motor and perceptual skill learning corresponds to procedural learning that can occur without conscious awareness. However, more work is required toward the direction of disentangling the perceptual from the motor component in the SRT task and other perceptuomotor tasks or everyday settings, as well as towards assessing the contribution of implicit and explicit knowledge alone, and/or in synergy when this is the case, at the different stages of learning (For a more systematic discussion on the knowledge types acquired in SRT tasks and the various types of human behavior they can elucidate see e.g., Robertson, 2007 andSchorn &Knowlton, 2022).…”
Section: Different Contexts and Applications Of Implicit Learningmentioning
confidence: 99%
“…Many studies that have used the SRT task have shown that motor and perceptual skill learning corresponds to procedural learning that can occur without conscious awareness. However, more work is required toward the direction of disentangling the perceptual from the motor component in the SRT task and other perceptuomotor tasks or everyday settings, as well as towards assessing the contribution of implicit and explicit knowledge alone, and/or in synergy when this is the case, at the different stages of learning (For a more systematic discussion on the knowledge types acquired in SRT tasks and the various types of human behavior they can elucidate see e.g., Robertson, 2007 andSchorn &Knowlton, 2022).…”
Section: Different Contexts and Applications Of Implicit Learningmentioning
confidence: 99%